5-HT2C Receptor Agonists for the Treatment of Obesity. Biological and Chemical Adventures - David Adams; Sven Taylor; Stephan Röver; Hans Richter; Jean-Marc Plancher; Jacques Mizrahi; Craig S. Malcolm; Antony R. Knight; Guy A. Kennett; Paul Hebeisen; Ian A. Cliffe; Anne Bourson; et al. (CHIMIA, 2004)
Obesity is a major risk factor in the development of conditions such as hypertension, hyperglycemia, dyslipidemia, coronary artery disease and cancer. There is increasing evidence suggesting an important role for the 5-HT2C receptor in appetite control. Collaboration between F. Hoffmann-La Roche Ltd and Vernalis Research Ltd has allowed rapid construction of a solid structure–activity relationship around a pyrroloindole core. A one-pot Sonogashira reaction followed by nucleophilic double cyclisation allows an elegant and expedient route to this central motif. Introduction of a (2S)-aminopropyl group in place of the aminoethyl endogenous ligand side-chain enhanced the affinity at the 5-HT2C receptor and reduced affinity towards monoamine oxidase enzymes (MAO). Sulfamidate reagents were found to be very effective for the introduction of the 2-aminopropyl moiety in a stereoselective manner. The substitution at position 5 (indole numbering) was found to be crucial for both affinity and selectivity. Pyrroloindoles bearing an alkoxyether in this position exhibit promising pharmacokinetic parameters in rodent and significant reduction of food intake, after per os application.